91 The production of sulfated 16-androstene steroids by porcine Leydig cells and their potential role in the development of boar taint. (5th December 2019) - Bone, Christine; Laderoute, Heidi; Brewer, Dyanne; Cameron, Jocelyn; Squires, E James
Abstract: Boar taint is a meat quality issue characterized by an off-odour or off-flavour in pork caused primarily by the accumulation of androstenone in the fat, but sensory estimates of boar taint do not always correlate with fat androstenone concentrations. However, these evaluations examine the sensory qualities of both the fat and lean tissue of heated pork products. Sulfated metabolites of androstenone are polar compounds that are abundantly produced by the Leydig cells of the testes, which may accumulate in more hydrophilic lean tissue. Therefore, the purpose of this study was to investigate the testicular metabolism of androstenone, which is responsible for the high production of sulfated androstenone metabolites. Leydig cells were isolated from 7-month-old Yorkshire, Duroc and terminal cross [Duroc x (Landrace x Yorkshire)] (n = 3) boars and incubated with radiolabeled androstenone for 8 hours. The proportion of sulfated metabolites produced was quantified using reverse phase high performance liquid chromatography (HPLC) and radioisotope detection. The sulfated metabolites were subsequently identified using liquid chromatography-mass spectrometry (LC-MS/MS). Statistical analysis was conducted using a one-way ANOVA in SAS. Following isolation and analysis with LC-MS/MS, the sulfated metabolites were identified as androstenol-3-sulfate and two major sulfated forms of androstenone. Additionally, removal of the sulfate group from these two sulfated forms of androstenone returned the parent compound androstenone, and not a hydroxylated metabolite. The average production of sulfated androstenol produced across all boars was 52.1±8.6%, which was not significantly different (P = 0.7) from the average production of sulfated androstenone (47.9±8.6%). The results of this study indicate that androstenone is directly sulfated, which allows these sulfated metabolites to function as steroid reservoirs that can enzymatically regenerate free androstenone within hydrophilic lean tissue. Alternatively, these metabolites may accumulate in the lean tissue, which we are proposing as a novel mechanism that contributes to the development of boar taint.